Sociological factors affecting trust development in virtual communities. (14th January 2008) - Daneshgar, Farhad; Ho, Sharon
This study explores development of trust by people participating in Virtual Communities (VCs). The broad question in this research is to investigate common factors responsible for trust development in both virtual and physical worlds. The main sociological factors that influence trust in physical communities have been hypothesised for their contribution to the development of trust in VCs. A quantitative online survey instrument was developed and applied to an online community based on existing literature on sociology under two major categories: 'personal-level' and 'contextual-level'. Results confirmed significant contribution of the factors at both personal-level' and 'contextual-level'. Results also confirm some of the existing findings in related areas.